PERAN DAKWAH ISLAMIYYAH DALAM KEHIDUPAN YANG DALAM ERA GLOBALISASI - Nurul Husaini (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
Islamic da'wah is an effort to spread the teachings of Islam to society through various media and approaches. In the era of globalization, da'wah faces new challenges and opportunities. This study aims to analyze effective da'wah strategies among the youth and their impact on their understanding of Islam. The methods used include literature review and interviews with experienced da'is. The results indicate that the use of social media and digital technology is highly effective in conveying da'wah messages. Inclusive and dialogic approaches are also key to engaging the youth in understanding Islamic values. However, challenges such as misinformation and negative stereotypes persist and need to be addressed. The study concludes by emphasizing the importance of innovation in da'wah methods and the need for collaboration among various societal elements to create an environment that supports the peaceful dissemination of Islamic teachings. Thus, Islamic da'wah can positively contribute to the formation of a more tolerant and respectful society.